Predictive value of low interleukin-33 in critically ill patients. (March 2018) - Krychtiuk, Konstantin A.; Stojkovic, Stefan; Lenz, Max; Brekalo, Mira; Huber, Kurt; Wojta, Johann; Heinz, Gottfried; Demyanets, Svitlana; Speidl, Walter S.
Highlights: In critically ill patients IL-33 is higher in 30-day survivors. Low levels of IL-33 and increased levels of sST2 additively predict mortality risk. sST2 correlated with both IL-6 and CRP in critically ill patients. IL-33 and sST2 in addition to APACHE II score could improve risk stratification. Abstract: Patients admitted to a medical intensive care unit (ICU) are characterized by an activated immune system and exhibit a high mortality rate irrespective of the underlying cause of admission. Interleukin (IL)-33 has been shown to be protective in experimental sepsis models and it has been demonstrated that circulating levels of its "decoy" receptor soluble ST2 (sST2) are associated with outcome in critically ill patients. The aim of the present study was to investigate whether circulating IL-33 is associated with 30-day mortality in patients admitted to a medical ICU. In this prospective, observational study, both IL-33 and sST2 levels were assessed in 223 consecutive patients at ICU admission using specific enzyme-linked immunosorbent assays (ELISAs). During the 30-day follow-up, 58 patients (26%) died. Circulating IL-33 was detectable in 166 patients and in 57 patients, serum IL-33 was below the detection limit. Both detectable IL-33 and sST2 below the median were strong predictors of survival in critically ill patients independent of acute physiology and chronic health evaluation II (APACHE II) score. IL-33 and sST2 predicted risk independent from each other. Patients with both, non-detectable levels of IL-33 and sST2 levels above the median, showed a dramatically increased mortality risk (HR 6.9 95% CI 3.0–16.2; p < 0.001). Low levels of IL-33 and increased levels of sST2 predict mortality risk in critically ill patients independent from each other and APACHE II score. Both together showed additive predictive value suggesting a pathogenic role of the IL-33/ST2 system in critically ill patients.